2016
DOI: 10.1177/0020852316654747
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and motivation: a qualitative study of transformational leadership and public service motivation

Abstract: Transformational leaders work to clarify a vision, share it with their employees and sustain it in the long run, and this is expected to result in increased employee public service motivation (PSM), that is, orientation towards doing good for others and society. Based on 48 in-depth interviews with 16 childcare leaders and 32 of their employees combined with 16 days of observation in these childcare centers, this article investigates the association between transformational leadership and PSM. When the leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 33 publications
(48 reference statements)
1
46
0
3
Order By: Relevance
“…Another mechanism through which transformational leadership works involves sharing the organization's vision (Andersen et al ). In a small‐scale qualitative study, Andersen et al () concluded that employees should not only understand the organization's vision but also experience that the vision is shared and maintained across the organization and that their jobs contribute to society.…”
Section: Lessons From the Researchmentioning
confidence: 99%
“…Another mechanism through which transformational leadership works involves sharing the organization's vision (Andersen et al ). In a small‐scale qualitative study, Andersen et al () concluded that employees should not only understand the organization's vision but also experience that the vision is shared and maintained across the organization and that their jobs contribute to society.…”
Section: Lessons From the Researchmentioning
confidence: 99%
“…One of the criticisms is that the PSM theory and measurement tool gives us little information about what motivates public sector employees and what actually causes motivation to ebb and flow in the careers of public sector employees [21]. Although few studies use unconventional research designs, such as experimental design by Bellé [17], longitudinal data by Vogel and Kroll [32], and a qualitative study by Andersen et al [77], a large amount of PSM scholarship is based on quantitative survey research design (p. 712) [23]. The survey research design, although widely used in various situations, is not good at drawing out more nuanced insights than other alternative ways of exploration which may be more suitable.…”
Section: Public Service Motivation (Psm)mentioning
confidence: 99%
“…However, it is not immediately clear that the broader social contributions of the same activities are equally vivid. Hence, even in the context of public service, perceptions of the societal impact of one's job can vary (Andersen et al ). This is important for the relationship between transformational leadership and value congruence because employees will only be able to identify with important aspects of the vision if they can establish a credible link between the vision and the contribution of their own job.…”
Section: The Moderating Role Of Perceived Societal Impactmentioning
confidence: 99%
“…Yet it is not immediately clear that employees working at the front lines clearly see how their work activities impact society at large. For instance, preschool teachers are certainly very attentive to the needs and well‐being of the children (Andersen et al ), but it is less obvious that the societal contributions of their work activities are equally vivid. Perceived societal impact refers to individuals' belief that they can contribute to the welfare of other people and society at large through their job (Bellé ).…”
mentioning
confidence: 99%